SOCIOLOGY OF LITERATURE AS APPROACH IN THE STUDY OF RELIGIOUS TEXTS - Atiq Aqiqotul Hasanah (Jurnal Bastra (Bahasa dan Sastra), 2022)
This study has aim to read and examine religious texts through sociology of literature approach, as well as to provide an academic basis about religious texts through the sociology of literature approach. The sociology of literature here is about Genetic Structuralism, while religious texts are works of interpretation which written by commentators. The type of this research is library research, namely research that is from library data, both primary and secondary, which includes materials on the sociology of literature and religious texts, such as interpretation works. The method of research and approach which used were descriptive-qualitative method with data collection technique through combining it, while the data analysis was deductive. The results of the study showed that the interpretation of religious texts can be analyzed with the theory of sociological literature through genetic structuralism aapproach because the work of interpretation has an intrinsic element of the text and also has an extrinsic element of text. The intrinsic elements of the interpretation text are strongly influenced by its extrinsic elements because the author of the interpretation is part of the community which faces social problems and express them in the structure of the text of interpretation. Some religious texts, especially works of interpretation texts which compiled by scholars can be analyzed and understood using sociological literature approach. Genetic structuralism as a branch of sociology of literature in operational research requires analyzing the intrinsic and extrinsic elements of the text. Meanwhile, Tafsir's work has both elements, namely text elements and some elements outside the text which are in the form of a socio-historical context in which the interpreter lives in it. In addition, looking at the works of interpretation which arranged in the form of text, it can be analyzed with literary sciences as approach.